Cardioprotection for Acute MI in Light of the CONDI2/ERIC-PPCI Trial: New Targets Needed - Joel P Giblett (Radcliffe Medical Media, 2020)
Protection against ischaemia–reperfusion injury after revascularisation in acute myocardial infarction remains an enigma. Many targets have been identified, but after the failure of the recent Effect of Remote Ischaemic Conditioning on Clinical Outcomes in ST-elevation Myocardial Infarction Patients Undergoing Primary Percutaneous Coronary Intervention (CONDI2/ERIC-PPCI) trial to show translation to clinical benefit, there is still no pharmacological or mechanical strategy that has translated to clinical practice. This article addresses the results of the CONDI2/ERIC-PPCI trial in the context of previous studies of ischaemic conditioning, and then considers the prospects for other potential targets of cardioprotection. Finally, the authors examine the pitfalls and challenges in trial design for future investigation of cardioprotective strategies. In particular, this article highlights the need for careful endpoint and patient selection, as well as the need to pay attention to the biology of cardioprotection during the study.